Investigating Undergraduate Students’ Outline and Essay Writing - Umi Hani; Mia Perlina (LPPM Universitas Bina Sarana Informatika, 2022)
Abstract - Writing an essay is quite tricky as it needs more than pouring all ideas in written arrangement. Those ideas must be gathered, organized, and planned to be arranged in an outline. The main goal of this study was aimed at examining the students’ outlines and their essays based on their outlines. To evaluate their outline, the framework was based on the outline checklist proposed by Zemach & Rumisek (2005). This study employed qualitative study and involved 30 students in the third semester of 2020/2021 academic year enrolled in the Essay Writing course, at English Department, Faculty of Letters, Universitas Pamulang (Unpam). The results of constructing an outline, it showed that the highest percentage (73%) in constructing an outline was in organization for paragraphs in the right order. On the other hand, insSupport for each main idea related to the thesis statement had the lowest percentage (40%). However, the results of generating essay writing based on their outline, there were 80% students who were successful following their outline when they created their essay. It can be concluded that most of students when they produced an outline and developed their ideas to write an essay from their outline, they followed their outline. On the other hand, they had challenge in developing support for Each main idea related to the thesis statement.